APLIKASI METODE ADAMS-BASHFORTH-MOULTON UNTUK MENGESTIMASI HASIL PRODUKSI UBI KAYU KOTA TEBING TINGGI - Daratullaila (Universitas Negeri Surabaya, 2025)
Cassava, a tuberous plant thriving in tropical countries, significantly contributes to the economy and food sector. According to a survey conducted by the Central Bureau of Statistics of Tebing Tinggi City in 2023, cassava stands out as the most cultivated agricultural commodity in Tebing Tinggi City. The aim of this research is to forecast the cassava production quantity using the Adams-Bashforth-Moulton method. The Adams-Bashforth-Moulton method is employed to numerically solve a specific point of a nonlinear differential equation with known initial values. Initially, the differential equation is solved using the fourth-order Runge-Kutta method to obtain four initial solutions, which are then substituted into the fourth-order Adams-Bashforth predictor equation. Subsequently, the forecasted value is corrected using the fourth-order Adams-Moulton corrector equation. The Adams-Moulton method is iteratively solved, with iteration termination occurring when the relative error falls below the stopping criterion of , involving 95 iterations within the interval [0, 95]. The fourth-order Adams-Bashforth-Moulton method can be utilized to obtain numerical solutions for cassava production in Tebing Tinggi City with a step size of h=1. The forecasting results reveal a monthly increase in cassava production in Tebing Tinggi City throughout the year 2024. Keywords: forecasting, Adams-Bashforth-Moulton, production, cassava.